Assessment of Public Transport Route: A Case of Lalitpur Yatayat - Koirala, Srijana; Agrawal, Sneha (Journal of Innovations in Engineering Education, 2021)
Lalitpur Yatayat, a public route from Patan Dhoka to Sukedhara round trip, is chosen for the study as previous study has not been made on the public transportation on this route. The objective of this paper is to analyse the route characterstics, identify problems and put proposals for future improvements. It discusses the various key characteristics of the route such as travel time in weekdays and weekend, hour span of service, no. of trips in a day, headway time and the major wards that it serves.The methodology and approaches followed for the execution of this work includes etic observation in site along with collection of relevant documents and conduct literature review of public tr. The main methodology followed in the site was in depth interview with the riders. Bilateral interactions, visual assessment and questionnaires were also some of the tools used. Moreover, the related articles, journals, reports acquired from the different sources, including internet and lecture reference are briefly reviewed.This report also highlights the current scenario and provision of bus stops in the route and propose assitional bus stops in the route.